2000
DOI: 10.1006/bbrc.2000.3641
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of (3Z)-Alkenals to 4-Hydroxy-(2E)-Alkenals in Plant Extracts: A Nonenzymatic Process

Abstract: There is large interest in 4-hydroxy-(2E)-alkenals because of their cytotoxicity in mammals. However, the biosynthetic pathway for these compounds has not been elucidated yet. In plants, 4-hydroxy-(2E)-alkenals were supposed to be derived by the subsequent actions of lipoxygenase and a peroxygenase on (3Z)-alkenals. The presence of 9-hydroxy-12-oxo-(10E)-dodecenoic acid (9-hydroxy-traumatin) in incubations of 12-oxo-(9Z)-dodecenoic acid (traumatin) in the absence of lipoxygenase or peroxygenase, has prompted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
3
35
0
1
Order By: Relevance
“…Meanwhile, the enzyme is on the membrane or transported to a wounded site. One of the versions is the presence of the HPL predecessor that is activated after cutting of the N-ter- [65]. 13-hPL genes expression was detected in the plant overground part while that of 9-HPL -in the root one.…”
Section: Regulation Of Lipoxygenase Signaling System Activitymentioning
confidence: 99%
“…Meanwhile, the enzyme is on the membrane or transported to a wounded site. One of the versions is the presence of the HPL predecessor that is activated after cutting of the N-ter- [65]. 13-hPL genes expression was detected in the plant overground part while that of 9-HPL -in the root one.…”
Section: Regulation Of Lipoxygenase Signaling System Activitymentioning
confidence: 99%
“…In observing the facile oxidation of 3Z-nonenal to 4-HPNE, we were prompted to propose a non-enzymatic pathway consisting of autoxidative formation of 9-HPODE from linoleic acid, followed by a Hock-type cleavage to give 3Z-nonenal, which undergoes rapid oxidation into 4-HPNE (12). It was shown that a route via 3Z-nonenal could account for HNE production in plant tissues (18). We surmised that the acid-catalyzed Hock cleavage could be achieved by the fatty acid carboxylate or other acidic moieties present under * This work was supported, in whole or in part, by National Institutes of Health Grants GM15431 and GM076592.…”
Section: Activation Of the Oxygenated Fatty Acidmentioning
confidence: 99%
“…ROS lead to the oxidation of unsaturated fatty acids in membranes, yielding LOOH (Taylor et al, 2004). These hydroperoxides are degraded nonenzymatically and cause the formation of carbonyl compounds, many of which are aldehydes (Noordermeer et al, 2000;Schneider et al, 2001). The moderate increases in MDA and LOOH were, therefore, indicating moderate oxidative stress.…”
Section: Cell Homeostasis and Detoxificationmentioning
confidence: 99%